Interview with Hazel Onsrud - Silka, Linda (Maine Policy Review, 2024)
An interview with Hazel Onsrud, an adult services librarian at Curtis Memorial Library in Brunswick, Maine. Onsrud is a winner of theALA’s 2024 Movers and Shakers Award. For the past eight years, she has spent most of her time on community-focused programing and collection development.